Modified copolymer alloy material, preparation method thereof and automobile grille

By performing the reactive extrusion technology such as Fuker alkylation reaction and combining lubricants in a twin-screw extruder, the problems of high brittleness and poor flame retardancy of SAN resin were solved, and a modified copolymer alloy material with good impact strength and flame retardant effect was prepared.

CN119684804APending Publication Date: 2025-03-25QINGDAO HAINA NEW MATERIAL CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510001516.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

SAN resin has high brittleness and poor flame retardancy, and the control of graft rate during its modification process is difficult, resulting in unstable performance, complex processing steps and residual organic solvents, affecting the product odor and appearance.

Method used

Using a preparation method without using organic solvents, the Fuker alkylation reaction is carried out under the action of a catalyst by styrene-acrylonitrile copolymer and chloroprene powder, and reactively extruded in a twin-screw extruder combined with lubricant, antioxidant and light stabilizer to form an inter-chain copolymer, and the modified copolymer alloy material is prepared by injection molding.

Benefits of technology

The prepared modified copolymer alloy material has low odor, simple preparation process, good impact strength and mechanical properties, and has flame retardant effect and low density, which is suitable for a wide range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention provides a modified copolymer alloy material, a preparation method thereof and an automobile grille, and belongs to the field of acrylonitrile-styrene copolymer materials. The preparation method of the modified copolymer alloy material comprises the following steps: firstly, carrying out Friedel-Crafts alkylation reaction on a styrene-acrylonitrile copolymer and chloroprene rubber powder under the action of a catalyst, and carrying out reactive extrusion on the reaction product, a lubricant, an antioxidant and a light stabilizer in a double-screw extruder to obtain an inter-chain copolymer; then the styrene-acrylonitrile copolymer, the chloroprene rubber powder, the catalyst, the lubricant, the antioxidant and the light stabilizer are mixed again for blending modification, the mechanical property and flame retardance of the modified copolymer alloy material are improved, no organic solvent is used in the preparation process, the processing temperature is low, the solvent does not need to be removed, operation is safe, and the preparation method is suitable for industrial production. The odor of the modified copolymer alloy material and the danger in the processing process are reduced, and the modified copolymer alloy material has environmental friendliness and safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of modified copolymer materials, in particular to a modified copolymer alloy material and a preparation method thereof and an automobile grille. Background Art

[0002] Styrene-acrylonitrile copolymer (SAN resin) is made of two monomers, styrene and acrylonitrile, through the bulk method, suspension method or emulsion method. It has the properties of acrylonitrile and styrene. Acrylonitrile makes the copolymer chemically stable and has processing fluidity, and has a certain surface hardness; styrene gives the copolymer rigidity and maintains transparency. SAN resin has a higher softening point than polystyrene, better chemical stability, and stronger stress cracking resistance, especially light resistance and high temperature resistance, which are greatly improved compared with polystyrene. It is an economical engineering and civil plastic. However, SAN resin is brittle and has poor fire resistance. With the increasing requirements for high-performance polymer materials, the application scope of SAN resin has also been greatly limited. Therefore, SAN resin needs to be modified to adapt to its application in the environment.

[0003] The modification of SAN resin in industry usually involves grafting rubber materials onto SAN resin, or directly melt-blending rubber materials or polar polymers with SAN resin to improve the toughness and impact strength of SAN resin. ABS resin is the most common material for SAN resin modification. It is a terpolymer obtained by copolymerization of three monomers: acrylonitrile (A), butadiene (B), and styrene (S). It is currently the most widely used general engineering plastic.

[0004] The grafting rate of SAN resin and rubber seriously affects the performance of SAN resin. The increase of grafting rate can increase the bonding force between SAN resin and rubber interface, but too high grafting rate may lead to the decrease of rubber elasticity, thereby reducing the impact strength. Therefore, it is necessary to control the appropriate grafting rate to obtain the best performance.

[0005] CN117986790A provides a method for preparing a shape memory 4D printing line suitable for fused deposition printing, which discloses a preparation process of a PB-g-SAN modifier, which specifically includes the following steps: step 1, adding deionized water, PB latex particles and KOH to a reactor under a protective atmosphere and a reaction temperature of 70°C, and stirring evenly under an alkaline environment; step 2, adding an azeotropic mixture of styrene, acrylonitrile and an initiator to the reactor in a continuous feeding manner to react and obtain a PB-g-SAN modifier.

[0006] In the process of SAN resin grafting modification, polybutene (PB) rubber is generally chopped and mixed with styrene and acrylonitrile to prepare PB solution, and then organic solvent and initiator are added to the reactor for preparation. This method has a complicated process and a large amount of organic solvent will remain during the production process, affecting the smell and appearance of the product.

[0007] Wei et al. Journal of Applied Polymer Science 》 Construction of inter-chain polymers and the investigation into Friedel-Crafts alkylation of styrene-acrylonitrile copolymers with chloroprene rubber and characterization The invention discloses the mechanism and preparation process of Friedel-Crafts alkylation reaction between styrene-acrylonitrile copolymer and chloroprene rubber powder.

[0008] In summary, SAN resin is very brittle and has poor flame retardancy. During the grafting modification of SAN resin, the control of the grafting rate leads to poor performance of the modified SAN resin. The complicated processing steps and a large amount of solvent residue, as well as the poor flame retardancy of the modified SAN resin, are still problems that need to be solved urgently. Summary of the invention

[0009] In view of the above problems, the present invention provides a modified copolymer alloy material and a preparation method thereof and an automobile grille. The modified copolymer alloy material does not use an organic solvent during the preparation process, the prepared material has low odor, and the preparation process is simple.

[0010] The invention provides a modified copolymer alloy material, wherein the modified copolymer alloy material is prepared by injection molding a mixed masterbatch; the modified copolymer alloy material has a tensile strength of 45-60 MPa, an elongation at break of 3-20%, a bending strength of 60-80 MPa, a bending modulus of 1900-2200 MPa, and a simply supported beam impact strength of 23°C of 2-5 kJ / m 2 , density is 1-2g / cm 3 , flame retardant grade is V1-V2; the mixed masterbatch is composed of styrene-acrylonitrile copolymer, chloroprene rubber powder, catalyst (MCl n ), lubricants, antioxidants and light stabilizers are prepared by extrusion in a twin-screw extruder; in the twin-screw extruder, the styrene-acrylonitrile copolymer and the chloroprene rubber powder undergo Friedel-Crafts alkylation reaction under the action of the catalyst.

[0011] Furthermore, based on the total mass of the mixed masterbatch, the components and contents in the mixed masterbatch are as follows: Styrene-acrylonitrile copolymer: 60-130wt%; Neoprene powder: 20-70wt%; Catalyst: 0.2-1wt%; Lubricant: 0.2-1wt%; Antioxidant: 0.2-1wt%; Light stabilizer: 0.2-1wt%.

[0012] Furthermore, the styrene content in the styrene-acrylonitrile copolymer accounts for 15-50% of the total mass percentage of the styrene-acrylonitrile copolymer.

[0013] Furthermore, the catalyst is a Lewis acid catalyst containing chloride ions.

[0014] Furthermore, the Friedel-Crafts alkylation reaction process is as follows: the benzene ring (C6H5~) in the styrene-acrylonitrile copolymer and the chlorine-containing component (R-Cl) in the chloroprene rubber powder are reacted in the presence of the catalyst (MCl n ) under the action of aromatic electrophilic substitution reaction, the specific process is: ; Where M is Al 3+ Sn 4+ , Fe 3+ 、C2H5Al 2+ One or more of, n is 2 or 3 or 4, that is, the catalyst (MCl n ) is one or more of AlCl3, AlCl3•6H2O, SnCl4, FeCl3, C2H5AlCl2; R-Cl is the chlorine-containing component in the chloroprene rubber powder, and R- is a group connected to the Cl ion.

[0015] Furthermore, the lubricant is one or more of oleic acid amide, stearic acid amide, vinyl bisstearamide (EBS), N,N-ethylene-bisstearamide, saturated fatty acids, unsaturated fatty acids, hydroxy fatty acids, zinc stearate, calcium stearate, barium stearate, pentaerythritol stearate (PETS), silicone oil, white mineral oil, liquid paraffin and polyethylene wax.

[0016] Furthermore, the antioxidant is one or more of tris[2,4-di-tert-butylphenyl]phosphite, diphenylamine, p-phenylenediamine, disulfide, 2,6-tert-butyl-4-methylphenol, didodecanol ester, didetradecyl ester, distearyl thiodipropionate (DSTP) and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0017] Further, the light stabilizer is one or more of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, o-hydroxybenzoic acid phenyl ester, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester.

[0018] The present invention also provides a method for preparing the modified copolymer alloy material, wherein each component is weighed according to the content of each component, and the preparation method comprises the following steps: Step 1, adding styrene-acrylonitrile copolymer, chloroprene rubber powder, catalyst, lubricant, antioxidant and light stabilizer into a high-speed mixer for blending, adding the blended mixture into a twin-screw extruder, and reactively extruding the mixture under nitrogen protection to obtain an interchain copolymer (SAN-CR); Step 2, adding the interchain copolymer, styrene-acrylonitrile copolymer, chloroprene rubber powder, lubricant, antioxidant and light stabilizer into a high-speed mixer for blending, and then adding the blended mixture into a twin-screw extruder for extrusion to obtain a mixed masterbatch; Step 3: injection molding the mixed masterbatch through an injection molding machine to obtain the modified copolymer alloy material.

[0019] Furthermore, in step 1, the mass ratio of the styrene-acrylonitrile copolymer, chloroprene rubber powder, catalyst, lubricant, antioxidant and light stabilizer is (50-80): (10-50): (0.1-0.5): (0.1-0.5): (0.1-0.5): (0.1-0.5).

[0020] Furthermore, in the step 1, the styrene content in the styrene-acrylonitrile copolymer accounts for 15-50% of the total mass percentage of the styrene-acrylonitrile copolymer.

[0021] Furthermore, the catalyst in step 1 is one or more of AlCl3, AlCl3•6H2O, SnCl4, FeCl3, and C2H5AlCl2.

[0022] Furthermore, the lubricant in step 1 is one or more of oleic acid amide, stearic acid amide, vinyl bisstearamide (EBS), N,N-ethylene-bisstearamide, saturated fatty acids, unsaturated fatty acids, hydroxy fatty acids, zinc stearate, calcium stearate, barium stearate, pentaerythritol stearate (PETS), silicone oil, white mineral oil, liquid paraffin and polyethylene wax.

[0023] Furthermore, the antioxidant in step 1 is one or more of tris[2,4-di-tert-butylphenyl]phosphite, diphenylamine, p-phenylenediamine, disulfide, 2,6-tert-butyl-4-methylphenol, didodecanol ester, didetradecyl ester, distearyl thiodipropionate (DSTP) and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0024] Furthermore, the light stabilizer in step 1 is one or more of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, o-hydroxybenzoic acid phenyl ester, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester.

[0025] Furthermore, the rotation speed of the high-speed mixer in step 1 is 250-450 rpm.

[0026] Furthermore, the blending time in step 1 is 3-5 minutes.

[0027] Furthermore, the screw speed of the twin-screw extruder in step 1 is 200-500 rpm.

[0028] Furthermore, the vacuum pressure of the twin-screw extruder in step 1 is -0.08 to -0.02 MPa.

[0029] Furthermore, the melt temperature of the twin-screw extruder in step 1 is 200-230°C.

[0030] Furthermore, the main engine current of the twin-screw extruder in step 1 is 45-60A.

[0031] Furthermore, the aspect ratio of the twin-screw extruder in step 1 is 60:1, and the feeding speed is 50-60 kg / h.

[0032] Furthermore, the feeding method of the twin-screw extruder in step 1 is feeding through a main feeding port, a first side feeding port, or a second side feeding port.

[0033] Further, the processing temperature of the twin-screw extruder in the step 1 is 170-200°C, which is divided into fourteen temperature zones, wherein the temperature of the first temperature zone is 170-180°C, the temperature of the second temperature zone is 180-185°C, the temperature of the third temperature zone is 185-190°C, the temperature of the fourth temperature zone is 185-190°C, the temperature of the fifth temperature zone is 185-190°C, the temperature of the sixth temperature zone is 190-195°C, the temperature of the seventh temperature zone is 185-190°C, the temperature of the eighth temperature zone is 180-185°C, the temperature of the ninth temperature zone is 180-185°C, the temperature of the tenth temperature zone is 185-190°C, the temperature of the eleventh temperature zone is 190-195°C, the temperature of the twelfth temperature zone is 195-200°C, the temperature of the thirteenth temperature zone is 195-200°C, and the temperature of the fourteenth temperature zone is 190-195°C.

[0034] Furthermore, the styrene-acrylonitrile copolymer and the chloroprene rubber powder in step 1 undergo a Friedel-Crafts alkylation reaction under the action of a catalyst, and are reactively extruded with a lubricant, an antioxidant and a light stabilizer in a twin-screw extruder.

[0035] Furthermore, in the step 2, the mass ratio of the interchain copolymer, styrene-acrylonitrile copolymer, chloroprene rubber powder, lubricant, antioxidant and light stabilizer is (60.4-72): (10-50): (10-20): (0.1-0.5): (0.1-0.5): (0.1-0.5).

[0036] Furthermore, in the step 2, the styrene content in the styrene-acrylonitrile copolymer accounts for 15-50% of the total mass percentage of the styrene-acrylonitrile copolymer.

[0037] Furthermore, the lubricant in step 2 is one or more of oleamide, stearic acid amide, vinyl bisstearamide (EBS), N,N-ethylene-bisstearamide, saturated fatty acids, unsaturated fatty acids, hydroxy fatty acids, zinc stearate, calcium stearate, barium stearate, pentaerythritol stearate (PETS), silicone oil, white mineral oil, liquid paraffin and polyethylene wax.

[0038] Furthermore, the antioxidant in step 2 is one or more of tris[2,4-di-tert-butylphenyl]phosphite, diphenylamine, p-phenylenediamine, disulfide, 2,6-tert-butyl-4-methylphenol, didodecanol ester, didetradecyl ester, distearyl thiodipropionate (DSTP) and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0039] Further, the light stabilizer in step 2 is one or more of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone, o-hydroxybenzoic acid phenyl ester, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole and 2-methyl-2-acrylic acid-2,2,6,6-tetramethyl-4-piperidinyl ester.

[0040] Furthermore, the rotation speed of the high-speed mixer in step 2 is 250-450 rpm.

[0041] Furthermore, the blending time in step 2 is 3-5 minutes.

[0042] Furthermore, the screw speed of the twin-screw extruder in step 2 is 200-500 rpm.

[0043] Furthermore, the vacuum pressure of the twin-screw extruder in step 2 is -0.08 to -0.02Mpa.

[0044] Furthermore, the melt temperature of the twin-screw extruder in step 2 is 200-230°C.

[0045] Furthermore, the main engine current of the twin-screw extruder in step 2 is 45-60A.

[0046] Furthermore, the aspect ratio of the twin-screw extruder in step 2 is 40:1, and the feeding speed is 30-40 kg / h.

[0047] Further, the processing temperature of the twin-screw extruder in the step 2 is 180-200°C, which is divided into ten temperature zones, wherein the temperature of the first temperature zone is 180-185°C, the temperature of the second temperature zone is 185-190°C, the temperature of the third temperature zone is 190-195°C, the temperature of the fourth temperature zone is 195-200°C, the temperature of the fifth temperature zone is 195-200°C, the temperature of the sixth temperature zone is 190-195°C, the temperature of the seventh temperature zone is 190-195°C, the temperature of the eighth temperature zone is 185-190°C, the temperature of the ninth temperature zone is 180-185°C, and the temperature of the tenth temperature zone is 185-190°C.

[0048] Furthermore, the interchain copolymer in step 2 is used as a compatibilizer to improve the compatibility of the styrene-acrylonitrile copolymer and the chloroprene rubber powder, and the lubricant, antioxidant and light stabilizer are mixed and extruded in a twin-screw extruder.

[0049] Furthermore, in step 3, the injection molding temperature of the injection molding machine is 200-300° C., and the injection molding pressure is 50-65 MPa.

[0050] The present invention also provides an automobile grille, which is prepared from the modified copolymer alloy material.

[0051] Beneficial effects of the present invention: 1. The modified copolymer alloy material of the present invention first undergoes Friedel-Crafts alkylation reaction between styrene-acrylonitrile copolymer and chloroprene rubber powder under the action of a catalyst, and then is reactively extruded with a lubricant, an antioxidant and a light stabilizer in a twin-screw extruder to obtain an interchain copolymer, and then the styrene-acrylonitrile copolymer, chloroprene rubber powder, a lubricant, an antioxidant and a light stabilizer are mixed again for blending modification. Since the compatibility of the styrene-acrylonitrile copolymer and the chloroprene rubber powder is poor, the interchain copolymer just serves as a compatibilizer for the styrene-acrylonitrile copolymer and the chloroprene rubber powder, and after being blended with the lubricant, the antioxidant and the light stabilizer, the impact strength and mechanical properties of the modified copolymer alloy material are improved; and the content of acrylonitrile in the styrene-acrylonitrile copolymer of the present invention is relatively high, wherein the nitrile group in acrylonitrile has solvent resistance and a strong bonding force with other groups; 2. In the preparation process of the modified copolymer alloy material of the present invention, no organic solvent is used and the processing temperature is low, there is no need to remove the solvent, the operation is relatively safe, the odor of the modified copolymer alloy material and the danger of the processing process are reduced, and it is environmentally friendly and safe; and in the preparation process of the interchain copolymer of the present invention, nitrogen protection is required to prevent the styrene-acrylonitrile copolymer and the chloroprene rubber powder from being oxidized into aldehydes and ketones by oxygen, thereby causing the material to yellow; 3. The modified copolymer alloy material of the present invention still has a flame retardant effect without adding a flame retardant, wherein the halogen in the chloroprene rubber powder can capture and eliminate these free radicals during the combustion process of the material, cut off the free radical chain reaction, control the combustion, and thus achieve the purpose of flame retardancy; 4. The preparation process of the modified copolymer alloy material of the present invention is simple, and only requires a two-step extrusion process. In the first extrusion process, a twin-screw extruder with a length-to-diameter ratio of 60:1 is used. The material is blended in the twin-screw extruder for a longer time, the reaction is more complete, and the reactive extrusion process is more thorough. The second basic process only uses a twin-screw extruder with a length-to-diameter ratio of 40:1 to ensure that the material has a higher performance retention rate and less thermal degradation during the blending process. The twin-screw extruder used in the present invention is a parallel twin-screw extruder, which is different from a conical twin-screw extruder. DETAILED DESCRIPTION

[0052] The invention is described in detail below with reference to the embodiments: The invention provides a modified copolymer alloy material and a preparation method thereof and an automobile grille, which greatly improves the impact resistance and flame retardancy of the modified copolymer alloy material through two-step mixing of styrene-acrylonitrile copolymer, chloroprene rubber powder, catalyst, lubricant, antioxidant and light stabilizer.

[0053] Example 1 The present embodiment provides a modified copolymer alloy material, which is prepared by injection molding a mixed masterbatch; the modified copolymer alloy material has a tensile strength of 51.5 MPa, an elongation at break of 18%, a flexural strength of 65 MPa, a flexural modulus of 2000 MPa, and a simply supported beam impact strength of 4.3 kJ / m at 23°C. 2 , density is 1.1g / cm 3 , flame retardant grade V1; the mixed masterbatch is composed of styrene-acrylonitrile copolymer, chloroprene rubber powder, catalyst (MCl n ), lubricants, antioxidants and light stabilizers are prepared by extrusion in a twin-screw extruder; in the twin-screw extruder, the styrene-acrylonitrile copolymer and the chloroprene rubber powder undergo Friedel-Crafts alkylation reaction under the action of the catalyst.

[0054] This embodiment also provides a method for preparing the modified copolymer alloy material, wherein each component is weighed according to its content, and the preparation method comprises the following steps: Step 1, adding 70 parts by weight of styrene-acrylonitrile copolymer, 30 parts by weight of chloroprene rubber powder, 0.5 parts by weight of catalyst, 0.5 parts by weight of lubricant, 0.3 parts by weight of antioxidant and 0.2 parts by weight of light stabilizer into a high-speed mixer, and blending at 250 r / min for 5 minutes; after blending, adding into a twin-screw extruder, and reactively extruding under nitrogen protection to obtain an interchain copolymer (SAN-CR); The screw speed of the twin-screw extruder in the step 1 is 200rpm, the vacuum pressure is -0.08MPa, the melt temperature is 220°C, the main engine current is 45A, the aspect ratio is 60:1, the feeding speed is 50kg / h, the feeding method is feeding at the main feeding port, the processing temperature of the twin-screw extruder is 180-200°C, and it is divided into fourteen temperature zones, wherein the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 185°C, the temperature of the third temperature zone is 190°C, the temperature of the fourth temperature zone is 190°C, the temperature of the fifth temperature zone is 190°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 190°C, the temperature of the eighth temperature zone is 185°C, the temperature of the ninth temperature zone is 185°C, the temperature of the tenth temperature zone is 190°C, the temperature of the eleventh temperature zone is 195°C, the temperature of the twelfth temperature zone is 200°C, the temperature of the thirteenth temperature zone is 200°C, and the temperature of the fourteenth temperature zone is 195°C; Step 2, adding 50 parts by weight of the interchain copolymer, 35 parts by weight of styrene-acrylonitrile copolymer, 15 parts by weight of chloroprene rubber powder, 0.5 parts by weight of lubricant, 0.3 parts by weight of antioxidant and 0.2 parts by weight of light stabilizer into a high-speed mixer, and blending for 5 minutes at 250 r / min; after blending, adding into a twin-screw extruder for extrusion to obtain a mixed masterbatch; The screw speed of the twin-screw extruder in step 2 is 200rpm, the vacuum pressure is -0.08MPa, the melt temperature is 220°C, the main engine current is 45A, the aspect ratio is 40:1, the feeding speed is 30kg / h, and the feeding method is feeding at the main feeding port. The processing temperature of the twin-screw extruder is 185-200°C, which is divided into ten temperature zones, wherein the temperature of the first temperature zone is 185°C, the temperature of the second temperature zone is 190°C, the temperature of the third temperature zone is 195°C, the temperature of the fourth temperature zone is 200°C, the temperature of the fifth temperature zone is 200°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 195°C, the temperature of the eighth temperature zone is 190°C, the temperature of the ninth temperature zone is 185°C, and the temperature of the tenth temperature zone is 190°C; Step 3: injection molding the mixed masterbatch at 200° C. and 50 MPa using an injection molding machine to obtain the modified copolymer alloy material.

[0055] In this embodiment, the styrene content in the styrene-acrylonitrile copolymer accounts for 15% of the total mass percentage of the styrene-acrylonitrile copolymer; the catalyst is AlCl3•6H2O; the lubricant is vinyl bisstearamide and pentaerythritol stearate; the antioxidant is pentaerythritol [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] ester and tris [2,4-di-tert-butylphenyl] phosphite; the light stabilizer is bis (2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0056] Example 2 The present embodiment provides a modified copolymer alloy material, which is prepared by injection molding a mixed masterbatch; the modified copolymer alloy material has a tensile strength of 60 MPa, an elongation at break of 4%, a flexural strength of 60 MPa, a flexural modulus of 2180 MPa, and a simply supported beam impact strength of 23°C of 2.1 kJ / m 2 , density is 1.1g / cm 3 , flame retardant grade V1; the mixed masterbatch is composed of styrene-acrylonitrile copolymer, chloroprene rubber powder, catalyst (MCl n ), lubricants, antioxidants and light stabilizers are prepared by extrusion in a twin-screw extruder; in the twin-screw extruder, the styrene-acrylonitrile copolymer and the chloroprene rubber powder undergo Friedel-Crafts alkylation reaction under the action of the catalyst.

[0057] This embodiment also provides a method for preparing the modified copolymer alloy material, wherein each component is weighed according to its content, and the preparation method comprises the following steps: Step 1, adding 70 parts by weight of styrene-acrylonitrile copolymer, 30 parts by weight of chloroprene rubber powder, 0.5 parts by weight of catalyst, 0.5 parts by weight of lubricant, 0.3 parts by weight of antioxidant and 0.2 parts by weight of light stabilizer into a high-speed mixer, and blending at 300 r / min for 4 minutes; after blending, adding into a twin-screw extruder, and reactively extruding under nitrogen protection to obtain an interchain copolymer (SAN-CR); The screw speed of the twin-screw extruder in step 1 is 300rpm, the vacuum pressure is -0.06MPa, the melt temperature is 230°C, the main engine current is 50A, the aspect ratio is 60:1, the feeding speed is 60kg / h, and the feeding method is feeding at the main feeding port. The processing temperature of the twin-screw extruder is 180-200°C, which is divided into fourteen temperature zones, wherein the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 185°C, the temperature of the third temperature zone is 190°C, the temperature of the fourth temperature zone is 190°C, the temperature of the fifth temperature zone is 190°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 190°C, the temperature of the eighth temperature zone is 185°C, the temperature of the ninth temperature zone is 185°C, the temperature of the tenth temperature zone is 190°C, the temperature of the eleventh temperature zone is 195°C, the temperature of the twelfth temperature zone is 200°C, the temperature of the thirteenth temperature zone is 200°C, and the temperature of the fourteenth temperature zone is 195°C; Step 2, adding 50 parts by weight of the interchain copolymer, 35 parts by weight of styrene-acrylonitrile copolymer, 15 parts by weight of chloroprene rubber powder, 0.5 parts by weight of lubricant, 0.3 parts by weight of antioxidant and 0.2 parts by weight of light stabilizer into a high-speed mixer, and blending at 300 r / min for 4 minutes; after blending, adding into a twin-screw extruder for extrusion to obtain a mixed masterbatch; The screw speed of the twin-screw extruder in step 2 is 300rpm, the vacuum pressure is -0.06MPa, the melt temperature is 230°C, the main engine current is 50A, the aspect ratio is 40:1, the feeding speed is 40kg / h, the feeding method is feeding at the main feeding port, and the processing temperature of the twin-screw extruder is 185-200°C, which is divided into ten temperature zones, wherein the temperature of the first temperature zone is 185°C, the temperature of the second temperature zone is 190°C, the temperature of the third temperature zone is 195°C, the temperature of the fourth temperature zone is 200°C, the temperature of the fifth temperature zone is 200°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 195°C, the temperature of the eighth temperature zone is 190°C, the temperature of the ninth temperature zone is 185°C, and the temperature of the tenth temperature zone is 190°C; Step 3: injection molding the mixed masterbatch at 250° C. and 55 MPa using an injection molding machine to obtain the modified copolymer alloy material.

[0058] In this embodiment, the styrene content in the styrene-acrylonitrile copolymer accounts for 15% of the total mass percentage of the styrene-acrylonitrile copolymer; the catalyst is SnCl4; the lubricant is vinyl bisstearamide and pentaerythritol stearate; the antioxidant is pentaerythritol [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] ester and tris [2,4-di-tert-butylphenyl] phosphite; the light stabilizer is bis (2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0059] Example 3 The present embodiment provides a modified copolymer alloy material, which is prepared by injection molding a mixed masterbatch; the modified copolymer alloy material has a tensile strength of 58.2 MPa, an elongation at break of 8%, a flexural strength of 72 MPa, a flexural modulus of 2150 MPa, and a simply supported beam impact strength of 3.1 kJ / m at 23°C. 2 , density is 1.1g / cm 3 , flame retardant grade V2; the mixed masterbatch is composed of styrene-acrylonitrile copolymer, chloroprene rubber powder, catalyst (MCl n ), lubricants, antioxidants and light stabilizers are prepared by extrusion in a twin-screw extruder; in the twin-screw extruder, the styrene-acrylonitrile copolymer and the chloroprene rubber powder undergo Friedel-Crafts alkylation reaction under the action of the catalyst.

[0060] This embodiment also provides a method for preparing the modified copolymer alloy material, wherein each component is weighed according to its content, and the preparation method comprises the following steps: Step 1, adding 70 parts by weight of styrene-acrylonitrile copolymer, 30 parts by weight of chloroprene rubber powder, 0.5 parts by weight of catalyst, 0.5 parts by weight of lubricant, 0.3 parts by weight of antioxidant and 0.2 parts by weight of light stabilizer into a high-speed mixer, and blending at 450 r / min for 3 minutes; after blending, adding into a twin-screw extruder, and reactively extruding under nitrogen protection to obtain an interchain copolymer (SAN-CR); The screw speed of the twin-screw extruder in the step 1 is 400rpm, the vacuum pressure is -0.02MPa, the melt temperature is 220°C, the main engine current is 60A, the aspect ratio is 60:1, the feeding speed is 50kg / h, the feeding method is feeding at the main feeding port, the processing temperature of the twin-screw extruder is 180-200°C, and it is divided into fourteen temperature zones, wherein the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 185°C, the temperature of the third temperature zone is 190°C, the temperature of the fourth temperature zone is 190°C, the temperature of the fifth temperature zone is 190°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 190°C, the temperature of the eighth temperature zone is 185°C, the temperature of the ninth temperature zone is 185°C, the temperature of the tenth temperature zone is 190°C, the temperature of the eleventh temperature zone is 195°C, the temperature of the twelfth temperature zone is 200°C, the temperature of the thirteenth temperature zone is 200°C, and the temperature of the fourteenth temperature zone is 195°C; Step 2, adding 50 parts by weight of the interchain copolymer, 35 parts by weight of styrene-acrylonitrile copolymer, 15 parts by weight of chloroprene rubber powder, 0.5 parts by weight of lubricant, 0.3 parts by weight of antioxidant and 0.2 parts by weight of light stabilizer into a high-speed mixer, and blending for 3 minutes at 400 r / min; after blending, adding into a twin-screw extruder for extrusion to obtain a mixed masterbatch; The screw speed of the twin-screw extruder in step 2 is 400rpm, the vacuum pressure is -0.02MPa, the melt temperature is 230°C, the main engine current is 60A, the aspect ratio is 40:1, the feeding speed is 30kg / h, and the feeding method is feeding at the main feeding port. The processing temperature of the twin-screw extruder is 185-200°C, which is divided into ten temperature zones, wherein the temperature of the first temperature zone is 185°C, the temperature of the second temperature zone is 190°C, the temperature of the third temperature zone is 195°C, the temperature of the fourth temperature zone is 200°C, the temperature of the fifth temperature zone is 200°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 195°C, the temperature of the eighth temperature zone is 190°C, the temperature of the ninth temperature zone is 185°C, and the temperature of the tenth temperature zone is 190°C; Step 3: injection molding the mixed masterbatch at 300° C. and 65 MPa using an injection molding machine to obtain the modified copolymer alloy material.

[0061] In this embodiment, the styrene content in the styrene-acrylonitrile copolymer accounts for 15% of the total mass percentage of the styrene-acrylonitrile copolymer; the catalyst is FeCl3; the lubricant is vinyl bisstearamide and pentaerythritol stearate; the antioxidant is pentaerythritol [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] ester and tris [2,4-di-tert-butylphenyl] phosphite; the light stabilizer is bis (2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0062] Example 4 The present embodiment provides a modified copolymer alloy material, which is prepared by injection molding a mixed masterbatch; the modified copolymer alloy material has a tensile strength of 49.6 MPa, an elongation at break of 6%, a flexural strength of 68 MPa, a flexural modulus of 1950 MPa, and a simply supported beam impact strength of 23°C of 2.7 kJ / m 2 , density is 1.1g / cm 3 , flame retardant grade V2; the mixed masterbatch is composed of styrene-acrylonitrile copolymer, chloroprene rubber powder, catalyst (MCl n ), lubricants, antioxidants and light stabilizers are prepared by extrusion in a twin-screw extruder; in the twin-screw extruder, the styrene-acrylonitrile copolymer and the chloroprene rubber powder undergo Friedel-Crafts alkylation reaction under the action of the catalyst.

[0063] This embodiment also provides a method for preparing the modified copolymer alloy material, wherein each component is weighed according to its content, and the preparation method comprises the following steps: Step 1, adding 70 parts by weight of styrene-acrylonitrile copolymer, 30 parts by weight of chloroprene rubber powder, 0.5 parts by weight of catalyst, 0.5 parts by weight of lubricant, 0.3 parts by weight of antioxidant and 0.2 parts by weight of light stabilizer into a high-speed mixer, and blending at 250 r / min for 5 minutes; after blending, adding into a twin-screw extruder, and reactively extruding under nitrogen protection to obtain an interchain copolymer (SAN-CR); The screw speed of the twin-screw extruder in the step 1 is 200rpm, the vacuum pressure is -0.08MPa, the melt temperature is 220°C, the main engine current is 45A, the aspect ratio is 60:1, the feeding speed is 50kg / h, the feeding method is feeding at the main feeding port, the processing temperature of the twin-screw extruder is 180-200°C, and it is divided into fourteen temperature zones, wherein the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 185°C, the temperature of the third temperature zone is 190°C, the temperature of the fourth temperature zone is 190°C, the temperature of the fifth temperature zone is 190°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 190°C, the temperature of the eighth temperature zone is 185°C, the temperature of the ninth temperature zone is 185°C, the temperature of the tenth temperature zone is 190°C, the temperature of the eleventh temperature zone is 195°C, the temperature of the twelfth temperature zone is 200°C, the temperature of the thirteenth temperature zone is 200°C, and the temperature of the fourteenth temperature zone is 195°C; Step 2, adding 50 parts by weight of the interchain copolymer, 35 parts by weight of styrene-acrylonitrile copolymer, 15 parts by weight of chloroprene rubber powder, 0.5 parts by weight of lubricant, 0.3 parts by weight of antioxidant and 0.2 parts by weight of light stabilizer into a high-speed mixer, and blending for 5 minutes at 250 r / min; after blending, adding into a twin-screw extruder for extrusion to obtain a mixed masterbatch; The screw speed of the twin-screw extruder in step 2 is 200rpm, the vacuum pressure is -0.08MPa, the melt temperature is 220°C, the main engine current is 45A, the aspect ratio is 40:1, the feeding speed is 30kg / h, and the feeding method is feeding at the main feeding port. The processing temperature of the twin-screw extruder is 185-200°C, which is divided into ten temperature zones, wherein the temperature of the first temperature zone is 185°C, the temperature of the second temperature zone is 190°C, the temperature of the third temperature zone is 195°C, the temperature of the fourth temperature zone is 200°C, the temperature of the fifth temperature zone is 200°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 195°C, the temperature of the eighth temperature zone is 190°C, the temperature of the ninth temperature zone is 185°C, and the temperature of the tenth temperature zone is 190°C; Step 3: injection molding the mixed masterbatch at 200° C. and 50 MPa using an injection molding machine to obtain the modified copolymer alloy material.

[0064] In this embodiment, the styrene content in the styrene-acrylonitrile copolymer accounts for 15% of the total mass percentage of the styrene-acrylonitrile copolymer; the catalyst is C2H5AlCl2; the lubricant is vinyl bisstearamide and pentaerythritol stearate; the antioxidant is pentaerythritol [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] ester and tris [2,4-di-tert-butylphenyl] phosphite; the bis (2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0065] Comparative Example 1 The comparative example provides a modified copolymer alloy material, which is prepared by injection molding a mixed masterbatch; the modified copolymer alloy material has a tensile strength of 50.6 MPa, an elongation at break of 8%, a flexural strength of 60 MPa, a flexural modulus of 1800 MPa, and a simply supported beam impact strength of 3.1 kJ / m at 23°C. 2 , density is 1.1g / cm 3 The mixed masterbatch is composed of styrene-acrylonitrile copolymer, chloroprene rubber powder and catalyst (MCl n ) is prepared by extrusion in a twin-screw extruder; in the twin-screw extruder, the styrene-acrylonitrile copolymer and the chloroprene rubber powder undergo a Friedel-Crafts alkylation reaction under the action of the catalyst.

[0066] This comparative example also provides a method for preparing the modified copolymer alloy material, wherein each component is weighed according to the content of each component, and the preparation method comprises the following steps: Step 1, adding 70 parts by weight of styrene-acrylonitrile copolymer, 30 parts by weight of chloroprene rubber powder and 0.5 parts by weight of catalyst into a high-speed mixer, and blending at 250 r / min for 5 minutes; after blending, adding into a twin-screw extruder, and reactively extruding under nitrogen protection to obtain an interchain copolymer (SAN-CR); The screw speed of the twin-screw extruder in the step 1 is 200rpm, the vacuum pressure is -0.08MPa, the melt temperature is 220°C, the main engine current is 45A, the aspect ratio is 60:1, the feeding speed is 50kg / h, the feeding method is feeding at the main feeding port, the processing temperature of the twin-screw extruder is 180-200°C, and it is divided into fourteen temperature zones, wherein the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 185°C, the temperature of the third temperature zone is 190°C, the temperature of the fourth temperature zone is 190°C, the temperature of the fifth temperature zone is 190°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 190°C, the temperature of the eighth temperature zone is 185°C, the temperature of the ninth temperature zone is 185°C, the temperature of the tenth temperature zone is 190°C, the temperature of the eleventh temperature zone is 195°C, the temperature of the twelfth temperature zone is 200°C, the temperature of the thirteenth temperature zone is 200°C, and the temperature of the fourteenth temperature zone is 195°C; Step 2, adding 50 parts by weight of the interchain copolymer, 35 parts by weight of styrene-acrylonitrile copolymer and 15 parts by weight of chloroprene rubber powder into a high-speed mixer, and blending them at 250 r / min for 5 minutes; after blending, adding them into a twin-screw extruder for extrusion to obtain a mixed masterbatch; The screw speed of the twin-screw extruder in step 2 is 200rpm, the vacuum pressure is -0.08MPa, the melt temperature is 220°C, the main engine current is 45A, the aspect ratio is 40:1, the feeding speed is 30kg / h, and the feeding method is feeding at the main feeding port. The processing temperature of the twin-screw extruder is 185-200°C, which is divided into ten temperature zones, wherein the temperature of the first temperature zone is 185°C, the temperature of the second temperature zone is 190°C, the temperature of the third temperature zone is 195°C, the temperature of the fourth temperature zone is 200°C, the temperature of the fifth temperature zone is 200°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 195°C, the temperature of the eighth temperature zone is 190°C, the temperature of the ninth temperature zone is 185°C, and the temperature of the tenth temperature zone is 190°C; Step 3: injection molding the mixed masterbatch at 200° C. and 50 MPa using an injection molding machine to obtain the modified copolymer alloy material.

[0067] In this comparative example, the styrene content in the styrene-acrylonitrile copolymer accounts for 15% of the total mass percentage of the styrene-acrylonitrile copolymer; the catalyst is AlCl3•6H2O.

[0068] Comparative Example 2 The comparative example provides a modified copolymer alloy material, which is prepared by injection molding a mixed masterbatch; the modified copolymer alloy material has a tensile strength of 49.2 MPa, an elongation at break of 10%, a flexural strength of 58 MPa, a flexural modulus of 1760 MPa, and a simply supported beam impact strength of 3.5 kJ / m at 23°C. 2 , density is 1.1g / cm 3 The mixed masterbatch is composed of styrene-acrylonitrile copolymer, chloroprene rubber powder, catalyst (MCl n ), lubricants, antioxidants and light stabilizers are prepared by extrusion in a twin-screw extruder; in the twin-screw extruder, the styrene-acrylonitrile copolymer and the chloroprene rubber powder undergo Friedel-Crafts alkylation reaction under the action of the catalyst.

[0069] This comparative example also provides a method for preparing the modified copolymer alloy material, wherein each component is weighed according to the content of each component, and the preparation method comprises the following steps: Step 1, adding 70 parts by weight of styrene-acrylonitrile copolymer, 30 parts by weight of chloroprene rubber powder, 0.5 parts by weight of catalyst, 0.5 parts by weight of lubricant, 0.3 parts by weight of antioxidant and 0.2 parts by weight of light stabilizer into a high-speed mixer, and blending at 250 r / min for 5 minutes; after blending, adding into a twin-screw extruder, and reactively extruding under nitrogen protection to obtain an interchain copolymer (SAN-CR); The screw speed of the twin-screw extruder in step 1 is 200rpm, the vacuum pressure is -0.08MPa, the melt temperature is 220°C, the main engine current is 45A, the aspect ratio is 40:1, the feeding speed is 50kg / h, and the feeding method is feeding at the main feeding port. The processing temperature of the twin-screw extruder is 180-200°C, which is divided into fourteen temperature zones, wherein the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 185°C, the temperature of the third temperature zone is 190°C, the temperature of the fourth temperature zone is 190°C, the temperature of the fifth temperature zone is 190°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 190°C, the temperature of the eighth temperature zone is 185°C, the temperature of the ninth temperature zone is 185°C, the temperature of the tenth temperature zone is 190°C, the temperature of the eleventh temperature zone is 195°C, the temperature of the twelfth temperature zone is 200°C, the temperature of the thirteenth temperature zone is 200°C, and the temperature of the fourteenth temperature zone is 195°C; Step 2, adding 50 parts by weight of the interchain copolymer, 35 parts by weight of styrene-acrylonitrile copolymer, 15 parts by weight of chloroprene rubber powder, 0.5 parts by weight of lubricant, 0.3 parts by weight of antioxidant and 0.2 parts by weight of light stabilizer into a high-speed mixer, and blending for 5 minutes at 250 r / min; after blending, adding into a twin-screw extruder for extrusion to obtain a mixed masterbatch; The screw speed of the twin-screw extruder in step 2 is 200rpm, the vacuum pressure is -0.08MPa, the melt temperature is 220°C, the main engine current is 45A, the aspect ratio is 40:1, the feeding speed is 30kg / h, and the feeding method is feeding at the main feeding port. The processing temperature of the twin-screw extruder is 185-200°C, which is divided into ten temperature zones, wherein the temperature of the first temperature zone is 185°C, the temperature of the second temperature zone is 190°C, the temperature of the third temperature zone is 195°C, the temperature of the fourth temperature zone is 200°C, the temperature of the fifth temperature zone is 200°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 195°C, the temperature of the eighth temperature zone is 190°C, the temperature of the ninth temperature zone is 185°C, and the temperature of the tenth temperature zone is 190°C; Step 3: injection molding the mixed masterbatch at 200° C. and 50 MPa using an injection molding machine to obtain the modified copolymer alloy material.

[0070] In this comparative example, the styrene content in the styrene-acrylonitrile copolymer accounts for 15% of the total mass percentage of the styrene-acrylonitrile copolymer; the catalyst is AlCl3•6H2O; the lubricant is vinyl bisstearamide and pentaerythritol stearate; the antioxidant is pentaerythritol [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] and tris[2,4-di-tert-butylphenyl] phosphite; the light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0071] Comparative Example 3 The comparative example provides a modified copolymer alloy material, which is prepared by injection molding a mixed masterbatch; the modified copolymer alloy material has a tensile strength of 45 MPa, an elongation at break of 3%, a flexural strength of 55 MPa, a flexural modulus of 1650 MPa, and a simply supported beam impact strength of 23°C of 2.5 kJ / m 2 , density is 1.1g / cm 3 The mixed masterbatch is composed of styrene-acrylonitrile copolymer, chloroprene rubber powder, catalyst (MCl n ), lubricants, antioxidants and light stabilizers are prepared by extrusion in a twin-screw extruder; in the twin-screw extruder, the styrene-acrylonitrile copolymer and the chloroprene rubber powder undergo Friedel-Crafts alkylation reaction under the action of the catalyst.

[0072] This comparative example also provides a method for preparing the modified copolymer alloy material, wherein each component is weighed according to the content of each component, and the preparation method comprises the following steps: Step 1, adding 70 parts by weight of styrene-acrylonitrile copolymer, 30 parts by weight of chloroprene rubber powder, 0.5 parts by weight of catalyst, 0.5 parts by weight of lubricant, 0.3 parts by weight of antioxidant and 0.2 parts by weight of light stabilizer into a high-speed mixer, and blending at 250 r / min for 5 minutes; after blending, adding into a twin-screw extruder, and reactively extruding under nitrogen protection to obtain an interchain copolymer (SAN-CR); The screw speed of the twin-screw extruder in the step 1 is 200rpm, the vacuum pressure is -0.08MPa, the melt temperature is 220°C, the main engine current is 45A, the aspect ratio is 60:1, the feeding speed is 50kg / h, the feeding method is feeding at the main feeding port, the processing temperature of the twin-screw extruder is 180-200°C, and it is divided into fourteen temperature zones, wherein the temperature of the first temperature zone is 180°C, the temperature of the second temperature zone is 185°C, the temperature of the third temperature zone is 190°C, the temperature of the fourth temperature zone is 190°C, the temperature of the fifth temperature zone is 190°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 190°C, the temperature of the eighth temperature zone is 185°C, the temperature of the ninth temperature zone is 185°C, the temperature of the tenth temperature zone is 190°C, the temperature of the eleventh temperature zone is 195°C, the temperature of the twelfth temperature zone is 200°C, the temperature of the thirteenth temperature zone is 200°C, and the temperature of the fourteenth temperature zone is 195°C; Step 2, adding 50 parts by weight of the interchain copolymer, 35 parts by weight of styrene-acrylonitrile copolymer, 15 parts by weight of chloroprene rubber powder, 0.5 parts by weight of lubricant, 0.3 parts by weight of antioxidant and 0.2 parts by weight of light stabilizer into a high-speed mixer, and blending for 5 minutes at 250 r / min; after blending, adding into a twin-screw extruder for extrusion to obtain a mixed masterbatch; The screw speed of the twin-screw extruder in step 2 is 200rpm, the vacuum pressure is -0.08MPa, the melt temperature is 220°C, the main engine current is 45A, the aspect ratio is 60:1, the feeding speed is 30kg / h, the feeding method is feeding at the main feeding port, and the processing temperature of the twin-screw extruder is 185-200°C, which is divided into ten temperature zones, wherein the temperature of the first temperature zone is 185°C, the temperature of the second temperature zone is 190°C, the temperature of the third temperature zone is 195°C, the temperature of the fourth temperature zone is 200°C, the temperature of the fifth temperature zone is 200°C, the temperature of the sixth temperature zone is 195°C, the temperature of the seventh temperature zone is 195°C, the temperature of the eighth temperature zone is 190°C, the temperature of the ninth temperature zone is 185°C, and the temperature of the tenth temperature zone is 190°C; Step 3: injection molding the mixed masterbatch at 200° C. and 50 MPa using an injection molding machine to obtain the modified copolymer alloy material.

[0073] In this comparative example, the styrene content in the styrene-acrylonitrile copolymer accounts for 15% of the total mass percentage of the styrene-acrylonitrile copolymer; the catalyst is AlCl3•6H2O; the lubricant is vinyl bisstearamide and pentaerythritol stearate; the antioxidant is pentaerythritol [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] ester, tris [2,4-di-tert-butylphenyl] phosphite; the light stabilizer is bis (2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0074] The styrene-acrylonitrile copolymers described in Examples 1-4 and Comparative Examples 1-3 of the present invention are from Chi Mei Company, model PN-128, and have a Mw of 1.34×10 5 ,Mn=6.5×10 5 ; The chloroprene rubber is from Shanna Company, model CR-3222, and its Mw=5.62×10 5 ,Mn=1.87×10 5 .

[0075] Table 1 Components and contents of the modified copolymer alloy materials described in Examples 1-4 and Comparative Examples 1-3

[0076] Table 2 Properties of the modified copolymer alloy materials described in Examples 1-4 and Comparative Examples 1-3

[0077] As shown in Table 2, the modified copolymer alloy material of the present invention has good mechanical properties, high flame retardancy, and good comprehensive performance. In Comparative Example 1, no lubricant, antioxidant or other additives are added, and its mechanical properties are greatly reduced, indicating that the lubricant, antioxidant and light stabilizer of the present invention are melt-extruded together with the modified copolymer alloy material, which synergistically improves the mechanical properties and flame retardancy of the material. In comparative example 2, the aspect ratio of the twin-screw extruder during melt extrusion in step 1 and step 2 is 40:1. At this time, due to the reduction in the aspect ratio of the twin-screw extruder in step 1, the melting time of the material in the twin-screw extruder becomes shorter, resulting in poor blending effect of the material, and the stability of the interchain copolymer finally obtained is poor, the performance is unstable, and the material is not completely melted, resulting in the failure to better increase the compatibility of the styrene-acrylonitrile copolymer and the chloroprene rubber powder when blended with the material in step 2, so the performance of the obtained modified copolymer alloy material is poor; In comparative example 3, the aspect ratio of the twin screw extruder during melt extrusion in step 1 and step 2 is 60:1. At this time, due to the increase in the aspect ratio of the twin screw extruder in step 2, the material is melted in the twin screw extruder for too long, and the catalytic effect of the catalyst is weakened, resulting in poor performance of the material. Comparative Example 4 is a pure styrene-acrylonitrile copolymer, which has poor mechanical properties and no flame retardancy.

[0078] Based on the above, it can be seen that the modified copolymer alloy material described in this patent has a wide range of applications, low cost, and extremely high market prospects.

[0079] The above description is only a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any modification or equivalent change made based on the technical essence of the present invention still falls within the scope of protection required by the present invention.

Claims

1. A modified copolymer alloy material, characterized in that: The modified copolymer alloy material is prepared by injection molding a mixed masterbatch; the modified copolymer alloy material has a tensile strength of 45-60MPa, an elongation at break of 3-20%, a flexural strength of 60-80MPa, a flexural modulus of 1900-2200MPa, and a simply supported beam impact strength of 23°C of 2-5kJ / m 2 , density is 1-2g / cm 3 , the flame retardant grade is V1-V2; the mixed masterbatch is prepared by extruding styrene-acrylonitrile copolymer, chloroprene rubber powder, catalyst, lubricant, antioxidant and light stabilizer in a twin-screw extruder; in the twin-screw extruder, the styrene-acrylonitrile copolymer and the chloroprene rubber powder undergo Friedel-Crafts alkylation reaction under the action of the catalyst.

2. The modified copolymer alloy material according to claim 1, characterized in that: Based on the total mass of the mixed masterbatch, the components and contents in the mixed masterbatch are as follows: Styrene-acrylonitrile copolymer: 60-130wt%; Neoprene powder: 20-70wt%; Catalyst: 0.2-1wt%; Lubricant: 0.2-1wt%; Antioxidant: 0.2-1wt%; Light stabilizer: 0.2-1wt%.

3. The modified copolymer alloy material according to claim 1, characterized in that: The styrene content in the styrene-acrylonitrile copolymer accounts for 15-50% of the total mass percentage of the styrene-acrylonitrile copolymer.

4. The modified copolymer alloy material according to claim 1, characterized in that: The catalyst is a Lewis acid catalyst containing chloride ions.

5. The modified copolymer alloy material according to claim 1, characterized in that: The process of the Friedel-Crafts alkylation reaction is: the benzene ring in the styrene-acrylonitrile copolymer and the chlorine-containing component in the chloroprene rubber powder undergo an aromatic electrophilic substitution reaction under the action of the catalyst, and the specific process is: ; Where M is Al 3+ Sn 4+ , Fe 3+ 、C2H5Al 2+ One or more of, n is 2 or 3 or 4, that is, the catalyst is one or more of AlCl3, AlCl3•6H2O, SnCl4, FeCl3, C2H5AlCl2; R-Cl is the chlorine-containing component in the chloroprene rubber powder, and R- is a group connected to the Cl ion.

6. A method for preparing the modified copolymer alloy material according to any one of claims 1 to 5, characterized in that: Weigh each component according to its content, and the preparation method comprises the following steps: Step 1, adding styrene-acrylonitrile copolymer, chloroprene rubber powder, catalyst, lubricant, antioxidant and light stabilizer into a high-speed mixer for blending, adding the blended mixture into a twin-screw extruder, and reactively extruding the mixture under nitrogen protection to obtain an interchain copolymer; Step 2, adding the interchain copolymer, styrene-acrylonitrile copolymer, chloroprene rubber powder, catalyst, lubricant, antioxidant and light stabilizer into a high-speed mixer for blending, and then adding the blended mixture into a twin-screw extruder for extrusion to obtain a mixed masterbatch; Step 3: injection molding the mixed masterbatch through an injection molding machine to obtain the modified copolymer alloy material.

7. The preparation method according to claim 6, characterized in that: The length-to-diameter ratio of the twin-screw extruder in step 1 is 60:1, and the feeding speed is 50-60 kg / h.

8. The preparation method according to claim 6, characterized in that: The feeding method of the twin-screw extruder in step 1 is feeding through a main feeding port, a first side feeding port, or a second side feeding port.

9. The preparation method according to claim 6, characterized in that: The aspect ratio of the twin-screw extruder in step 2 is 40:1, and the feeding speed is 30-40 kg / h.

10. An automobile grille, characterized in that: The automobile grille is made of the modified copolymer alloy material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method of shape memory 4D printing line suitable for fused deposition printing

    CN117986790A